How Water-Smart Agricultural Solutions can Help us Stall Desertification and Thrive in the Face of Future Droughts - Palay, Isis (International Water Management Institute, 2022)
The blog was published as part of CGIAR's celebration of World Day to Combat Desertification and Drought. IT highlights revelations from a scientific journal article that for the sixth time, a new planetary boundary was crossed